Second Language Teaching With STEM - Crum, Sibel (Frontiers in Education, 2022)
The American Council on the Teaching of Foreign Languages World-Readiness Standards for Learning Languages, also known as ACTFL 5 Cs (National Standards Collaborative Board, 2015), aims to guide pre-kindergarten through higher education second language (L2) educators in what L2 learners at every level should do to progress in each standard. The ACTFL’s 5Cs includes five goal areas: Communication, Cultures, Connections, Comparisons, and Communities. Empirical research has shown that of these standards, Connections, where the languages are connected to academic disciplines for strengthening the learning, is one of the least utilized standards in L2 classrooms. Incorporating Science, Technology, Engineering, and Mathematics (STEM) as the connection discipline can help post secondary language learners in STEM and non-STEM fields develop the ability to effectively communicate technical and scientific STEM content within global STEM markets. This paper discusses the rationale for and the need to utilize the ACTFL’s Connections standards through STEM to grow and sustain L2 learners’ advanced language proficiency, as well as their employability and effectiveness in a highly competitive global work environment.